Internalisasi Sikap Toleransi Siswa Madrasah di Lingkungan Vihara Avalokitesvara - Ridho, Ali (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2018)
The research about the intenalization of the Students’ tolerance attitudes conducted at Madarsah Diniyah Miftahul Qulub III, Candi hamlet, Polagan Village, Galis district, Pamekasan regency was conducted to find out the objective condition of Madrasah Diniyah Miftahul Qulub III so that it could be used as a role model for the concept of learning in a multicultural area. In addition, this research is to find out about the things that Madrasah do in the effort to internalize students 'tolerance attitudes and to explain the impact of the steps to internalize students' tolerance attitudes conducted by Madrasah Diniyah Miftahul Qulub III. This research study used a qualitative approach with the primary instrument (main) used is an interview instrument (interview), while documentation and observation are only as supporters. While the type of research that will be used is a case study by means of descriptive analysis, namely by studying cases or phenomena related to the internalization of the tolerance attitude of madrasah students in the Vihara environment. From the results of this study, it was found that the internalization of the tolerance attitude of students in the Madrasah Diniyah (MD) Miftahul Qulub could be a role model for another madrasah. Because the building of tolerance continues to be driven by all components of society, especially madrasah stakeholders. Furthermore, the implementation of internalization includes the subject matter, namely the subjects of the Taisirul Khallaq book and Akhlakul lilbanin, which both emphasize the muamalah relationship which orientation is manifested in the form of amaliyah in students' daily lives, so that harmony will continue to be established. While the impact of the internalization of student tolerance is very pronounced in the hamlet of Candi, where the multicultural and multi-ethnic and religious regions are truly normal and harmonious. So based on this research, this locus is worthy to be used as a reference and even become an icon of tolerant madrasah in this country.